Conventional Decompression Remains the Gold Standard for Treating Lumbar Spinal Stenosis - Nierengarten, Mary Beth (MD Conference Express, 2015)
Surgical interspinous implants have been used to treat intermittent neurogenic claudication in patients with lumbar spinal stenosis. Some evidence has suggested it provided better outcomes compared with no (conservative) treatment. This article presents the 2-year results of the Surgical Interspinous Implant versus Conventional Decompression for Lumbar Spinal Stenosis trial that compared surgical interspinous implants to conventional decompression for patients with 1- or 2-level lumbar spinal stenosis.